MICROALGAE CHLAMYDOMONAS REINHARDTII VARIANT HAVING INCREASED CONTENTS OF BIOMASS, STARCH, AND LIPID THROUGH GAMMA IRRADIATION, AND A USE THEREOF - LIM, JONG MIN; HWANGBO, KWON; MIN, SUNG RAN; AHN, JOON-WOO; JEONG, WON JOONG (2015)
The present invention relates to a microalgae Chlamydomonas reinhardtii variant having increased contents of biomass, starch, and lipid through gamma irradiation, and a use thereof. The present invention provides microalgae which are appropriate to be used as economical biomass with increased bio-energy productivity, and the microalgae can be favorably used to produce lipid for biodiesel and starch for bio-ethanol. La présente invention concerne un variant de micro-algues Chlamydomonas reinhardtii présentant une teneur accrue en biomasse, en amidon et en lipide au moyen d'une irradiation gamma, et son utilisation. La présente invention concerne des micro-algues qui sont appropriées à une utilisation en tant que biomasse économique ayant une meilleure productivité de bio-énergie ; les micro-algues peuvent être utilisées favorablement pour produire un lipide pour du biodiesel et de l'amidon pour du bio-éthanol. 본 발명은 감마선 조사에 의해 바이오매스, 전분 및 지질 함량이 증진된 미세조류 클라미도모나스 레인하드티아이(Chlamydomonas reinhardtii) 변이체 및 이의 용도에 관한 것으로, 본 발명에 의해 바이오에너지 생산성이 높아진 경제적인 바이오매스로 사용되기에 적합한 미세조류를 제공하며, 상기 미세조류는 바이오디젤용 지질 생산 및 바이오에탄올용 전분 생산에 유용하게 이용될 수 있다.